2019
DOI: 10.1080/13676261.2019.1636945
|View full text |Cite
|
Sign up to set email alerts
|

Young, successful, precarious? Precariousness at the entry stage of employment careers in Germany

Abstract: The article investigates entry-stage employment trajectories of young people in Germany, asking whether transitions into continuous employment indicate successful labour market integration. Applying a novel multidimensional approach to precariousness to individuals' employment and household trajectories, we understand entry-stage employment trajectories holistically. The balanced-panel sample is drawn from the German SocioEconomic Panel, with a focus on young men and women between 15 and 25 years of age in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
(40 reference statements)
1
9
1
1
Order By: Relevance
“…Records of data for access to resources and economics are crucial to ensure that both current unemployment and work experience at university are recognized by employers for reference (Roberts and Zhen, 2017). According to Stuth and Jahn (2020), lack of work experience is one of the major obstacles that prevent young people from getting a job. In this regard, there is a stream of youths leaving their studies to seek work experience.…”
Section: Education Training and Work Experiencementioning
confidence: 99%
“…Records of data for access to resources and economics are crucial to ensure that both current unemployment and work experience at university are recognized by employers for reference (Roberts and Zhen, 2017). According to Stuth and Jahn (2020), lack of work experience is one of the major obstacles that prevent young people from getting a job. In this regard, there is a stream of youths leaving their studies to seek work experience.…”
Section: Education Training and Work Experiencementioning
confidence: 99%
“…Of concern, more than half of the participants in our study reported that their workplace support needs were unmet. Our findings provide evidence that young workers with rheumatic disease may start their career in work environments where supports are less accessible (18,35). Results can be explained by Canadian labor market analyses, which show that, when compared to older age groups, young adults are more likely to be employed precariously and in jobs where formal accommodations and extended health benefits are less likely to be provided (20,36).…”
Section: Discussionmentioning
confidence: 87%
“…While precarious living and working conditions used to be the challenge for the poor, Isabel Lorey (2015) argues that precarity has become a 'normal' experience (p. 63). Especially for young people who aspires to make a creative career, braving a precarious start, if not a precarious life, seems to be a prerequisite (Stuth & Jahn, 2019). As encapsulated in the terms 'aspirational labour', 'hope labourer' and the likes, many young creative workers are prepared to negotiate 'the temporal relationship between present experience and future aspirations' and 'shifts costs and risks' in order to maintain their aspirations and hopes of a better career and a better future (Kuehn & Corrigan, 2013, p. 11).…”
Section: Aspriation Precarity and Failurementioning
confidence: 99%